Acoustic Analysis of Formants at the Intersections of /n/ with Assimilated Occlusives (2019)
This article finds out which is the trace in the spectrogram of the trajectories of the first and second formants, at the intersections of the segments of /n/ followed by the bilabial and velar occlusive consonant in sequences of regressive assimilation, by means of the analysis voice of Praat software. The sample is extracted from the spontaneous speech of 18 people of Tunja (11 women and 7 men). From the analysis of the spectrograms three patterns leave for the sequences [mp], three for [mb], two for [ŋk] and one for [ŋg], according to the path of F1 and F2 at the intersection of the segments studied, occurred in the explosion bar of the occlusive consonant, where in all cases the two formants show rise or fall with respect to their travel. It is also concluded that according to the route of F1 and F2 there is no categorical certainty with which it can be identified if it is a bilabial or velar segment according to the spectrogram; however, there are some trends.